Public health research and practice in Africa - Abdu Ibrahim (AOSIS, 2010)
We are delighted to present the maiden edition of the Journal of Public Health in Africa (JPHIA). Like most great innovations, the idea behind JPHIA was spontaneously conceived upon observing the precarious state of public health care delivery in the African continent. The JPHIA is set up as non-profit making open source that will compete with other world class journals. The strength of JPHIA is in the people behind the journal's existence as well as the teeming interested readership. The journal will be published online and quarterly. No effort will be spared in ensuring that we publish high quality refereed materials despite our limited resources at this point.